Passive exercise increases cerebral blood flow velocity and supports a postexercise executive function benefit. (3rd July 2022) - Shirzad, Mustafa; Tari, Benjamin; Dalton, Connor; Van Riesen, James; Marsala, Michael J.; Heath, Matthew
Abstract: Executive function entails high‐level cognitive control supporting activities of daily living. Literature has shown that a single‐bout of exercise involving volitional muscle activation (i.e., active exercise) improves executive function and that an increase in cerebral blood flow (CBF) may contribute to this benefit. It is, however, unknown whether non‐volitional exercise (i.e., passive exercise) wherein an individual's limbs are moved via an external force elicits a similar executive function benefit. This is a salient question given that proprioceptive and feedforward drive from passive exercise increases CBF independent of the metabolic demands of active exercise. Here, in a procedural validation participants ( n = 2) used a cycle ergometer to complete separate 20‐min active and passive (via mechanically driven flywheel) exercise conditions and a non‐exercise control condition. Electromyography showed that passive exercise did not increase agonist muscle activation or increase ventilation or gas exchange variables (i.e., V̇O2 and V̇CO2 ). In a main experiment participants ( n = 28) completed the same exercise and control conditions and transcranial Doppler ultrasound showed that active and passive exercise (but not the control condition) increased CBF through the middle cerebral artery ( p s <.001); albeit the magnitude was less during passive exercise. Notably, antisaccade reaction times prior to and immediately after each condition showed that active ( p < .001) and passive ( p = .034) exercise improved an oculomotor‐based measure of executive function, whereas no benefit was observed in the control condition ( p = .85). Accordingly, results evince that passive exercise 'boosts' an oculomotor‐based measure of executive function and supports convergent evidence that increased CBF mediates this benefit. Abstract : The present findings show that passive exercise – wherein the flywheel of a cycle ergometer is mechanically driven – increases cerebral blood flow and engenders a postexercise benefit to executive function. These findings support a myriad of studies involving active exercise and demonstrate that an increase in cerebral blood flow independent of the metabolic costs of active exercise supports an executive function benefit.